United Arab Emirates No. 1 (2017) Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the United Arab Emirates Concerning Air Services. Abu Dhabi, 21 October 2014. ([2017-03-07]) - Unknown
No abstract available